The Influence of Education Level and Compensation on Employee Performance at the Regional Financial and Asset Management Agency in Arfak Mountains Regency - Torey, Melanesia Ferdinanda; Resi, Yohanes Damaskus; Mansoara, Nelson (Economics and Digital Business Review, 2025)
This study aims to analyse the influence of education level and compensation on employee performance at the Regional Financial and Asset Management Agency in Arfak Mountains Regency. A quantitative approach was used, involving data collection through surveys distributed to employees. The variables examined include education level, compensation, and their impact on performance. The findings reveal that education level significantly affects employees' ability to perform tasks, particularly in areas requiring technical skills and knowledge. Compensation also plays a critical role, as adequate and fair compensation motivates employees to improve their productivity and job satisfaction. Furthermore, the combination of higher education levels and well-structured compensation systems results in optimal performance. The study concludes that improving employee education and ensuring appropriate compensation can enhance overall organizational effectiveness. Recommendations include implementing training programs to upgrade employee competencies and revising compensation structures to align with performance goals, as well as exploring the potential impact of other factors, such as job satisfaction, work environment, and career development opportunities, on employee performance.